Seleccionando un Nombre para un Club 4-H - Marilyn N. Norman; Joy C. Jordan (EDIS)
4HS-FS101.7-Spn, a 2-page fact sheet by Marilyn N. Norman and Joy C. Jordan, is the Spanish language version of 4HS-FS101.7/4H240 Selecting a Name for a 4-H Club. It describes some considerations to make when selecting a name, and basic decision-making steps clubs can take to choose a name. Published by the UF 4-H Youth Development Program, August 2009.